2022
DOI: 10.1073/pnas.2201460119
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genetic toolkit helps dissect a global stress response in the early-branching species Fusobacterium nucleatum

Abstract: Fusobacterium nucleatum , long known as a common oral microbe, has recently garnered attention for its ability to colonize tissues and tumors elsewhere in the human body. Clinical and epidemiological research has now firmly established F. nucleatum as an oncomicrobe associated with several major cancer types. However, with the current research focus on host associations, little is known about gene regulation in F. nucleatum itself, including global st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 104 publications
3
50
0
Order By: Relevance
“…MazF has been used as a counterselection marker in other Gram-positive and Gram-negative bacteria (22). As we prepared this manuscript, a MazF-mediated counterselection strategy was reported in F. nucleatum (50). They used a tetracycline-inducible system to control the MazF expression in F. nucleatum .…”
Section: Discussionmentioning
confidence: 99%
“…MazF has been used as a counterselection marker in other Gram-positive and Gram-negative bacteria (22). As we prepared this manuscript, a MazF-mediated counterselection strategy was reported in F. nucleatum (50). They used a tetracycline-inducible system to control the MazF expression in F. nucleatum .…”
Section: Discussionmentioning
confidence: 99%
“…To increase the number of differentially labelled species in the model, additional fluorochromes might be looked at. Very recently, Ponath et al [52] developed several genetic tools for F. nucleatum including four distinct fluorescent proteins. Additionally, the oxygen independent HaloTag [53] or CLIP-tag [54]-a SNAP-variant [55]-seems to be worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, type I SPase is considered to be an attractive target (50,51). F. nucleatum possesses a LepB homolog, and a recent study revealed by RNA-seq that lepB is controlled by σ E , a mediator of an oxygeninduced response (27). However, no genetic study of lepB in F. nucleatum has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The F. nucleatum strain ATCC 23726 genome contains a gene locus annotated as lepB (27) (HMPREEF0397_0712, accessible at http://img.jgi.doe.gov/). We reasoned that this LepB might interact with RadD's signal peptide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation